Experimental seismic performance of multi- panel precast hollow core walls in warehouse buildings / Nor Hayati Abdul Hamid - Abdul Hamid, Nor Hayati (2006)
The seismic resistance ofa superassemblage of precast hollow core wall units for warehouses is investigated. The superassemblage consists of six prestressed concrete 1.2m wide hollow core units. Two of the units are tied to the foundation via unbonded vertical tendons while the other four units primarily act as "non-structural" cladding. The superassemblage represents the wall of a single storey warehouse type structure. The longitudinal unbonded prestressing tendons consist of regular thread-bars with an in-series portion of those bars possessing a reduced diameter to act as 'fuses ". Prior to testing, the fuse-bars are prestressed to 50% of their yield capacity. The multi-panel wall is tested under several different conditions: in-plane quasi-static reverse cyclic loading with different sizes of fuse-bars; and with and without rubber block spacers and sealant between units. Experimental results demonstrate that smaller diameter fuses lead to superior behaviour, as foundation uplift is inhibited. No structural damage occurs up to the experimental ± 4% drift limit. Some minor non-structural distress is observed to commence with sealant failure at 3% drift. This damage. however, is inexpensive to repair. Results also show that the hysteretic energy absorption that arises from the yielding tendons as well as the interacting rubber spacers and panel sealants provides an equivalent viscous damping factor of 10% at design drift amplitude of 2%. The overall good performance of the multi-panel wall system well satisfies the requirements of an emerging seismic Damage Avoidance Design (DAD) philosophy.